Reference material certification of chinese cabbage composition for selenium, nitrogen, phosphorus and potassium content - D. A. Chupakhin; V. A. Orlova; Yu. A. Karpov (Стандартные образцы)
Rationale. The reference material of composition with the established metrological characteristics including a certified value and an expanded uncertainty is necessary to ensure an effective accuracy and precision control of results of element composition determination in food ingredients and products. This paper represents the development of a reference material of food crop composition for selenium, nitrogen, phosphorus and potassium content. Methods. To identify the selenium the hybrid atomic absorption method was used, to identify the nitrogen and phosphorus the photometric method was used, to determine the potassium flame-photometric method was used. When determining the metrological characteristics of the reference material the Russian national instructions and recommendations MI 3174-2009 and P 50.2.058-2007 were applied. Results. Based on the research findings the reference material of Chinese cabbage composition with a certified value and an expanded uncertainty was developed: for selenium 0.044 ± 0.017 mg/kg; for nitrogen 4.09 ± 0.27 %; for phosphorus 0.69 ± 0.14 %; for potassium 2.87 ± 0.22 %.